Assessment of socio-economic status, farming and breeding practices and major constraints of indigenous sheep farming in Tangail district, Bangladesh - CHOUDHURY, MD PANIR; HUDA, MD NAZMUL; PEHAN, ESHTIAK AHAMED; SHEJUTY, SHAHANAJ FERDOUSI; FERDOUSHI, FARIA BINTE (The Indian Journal of Animal Sciences, 2026)
The present study was conducted to assess the socio-economic profile, husbandry practices and challenges of sheep rearing in Tangail District, Bangladesh. The study followed a cross-sectional survey design and data were analyzed using descriptive statistics. Data were collected from 131 sheep-rearing farmers across 13 unions using a pre-tested questionnaire administered through face-to-face interviews. The majority of the farmers were female (82.84%), predominantly Muslim (84.73%), with 71.75% having no formal education. Most farmers (59.54%) primarily relied on agriculture for their livelihoods. Farmers had an average landholding of 73.54 decimals with average annual income of 78,574 BDT. The average sheep rearing experience was 4.83 years, reflecting moderate expertise in sheep husbandry. Farmers reared mainly indigenous sheep with an average flock size of 3.76 animals per household, with ewes comprising 54.60% of the total population. Semi-intensive feeding (76.17%) and natural mating (100%) were the predominant husbandry and breeding practices, with 72.31% relying on neighbours’ rams to bred their ewes. Reproductive performance was satisfactory, with a litter size of 2.13 and a service per conception rate of 1.10. Farmers demonstrated limited awareness and adoption of pre- and post-lambing management practices for sheep. Preventive health measures were minimal, as vaccination and deworming coverage were only 1.54% and 10%, respectively. Major health issues included diarrhoea, enteritis, and pneumonia, often linked to shared housing with cattle. These findings underscore the need for targeted extension services, organized breeding programs, farmertraining and improved veterinary care to boost sheep productivity and improve the livelihoods of farmers in the region.